Apport Des Images Satellites MODIS Dans L’étude De L’évolution De La Végétation Forestière De l’Est Algérien - Laala Ahmed; Alatou Djamel; Adimi Amina (European Scientific Journal, ESJ, 2016)
The monitoring of forest dynamics is needed to better quantify the intensity of climate change and their impacted on forest resources of Algeria. The NDVI (Normalized Difference Vegetation Index) was often used to take this step. It is considered a fluctuating parameter in space and in time, very used today to measure the physiological activity of plants and characterize the vigor of vegetation. In this study we tried to characterize the one hand the spatial and temporal variability of NDVI of forest ecosystems of eastern Algeria and also spatially identify via statistical calculations the stressed forest parcels where chlorophyll activity leaves shows fluctuations and anomalies. The data used are those of the spectral index NDVI MODIS sensor for detecting photosynthetic signal returned by the tree canopy. It appears from this study that the vegetative activity of the forest ecosystems of eastern Algeria is always strong in the coastal massifs and decreases according to a latitudinal gradient oriented approximately North-South. In terms of the ecosystems, this activity is greater for deciduous stands than for softwoods. Moreover, the mapping of the standard deviation of NDVI allowed us, first, to spatially discriminate stressed forest parcels that are considered priorities for the establishment of effective conservation strategy and, secondly, to identify the most threatened tree species that requires a rapid response and collaboration between the institutions concerned to protect it.